Selection of T cell clones expressing high-affinity public TCRs within Human cytomegalovirus-specific CD8 T cell responses. - Trautmann, L; Rimbert, M; Echasserieau, K; Saulquin, X; Neveu, B; Dechanet, J; Cerundolo, V; Bonneville, M (2005)
Assessment of clonal diversity of T cell responses against human CMV (HCMV), a major cause of morbidity in immunodepressed patients, provides important insights into the molecular basis of T cell immunodominance, and has also clinical implications for the immunomonitoring and immunotherapy of HCMV infections. We performed an in-depth molecular and functional characterization of CD8 T cells directed against an immunodominant HLA-A2-restricted epitope derived from HCMV protein pp65 (NLV/A2) in steady state and pathological situations associated with HCMV reactivation. NLV/A2-specific T cells in healthy HCMV-seropositive donors showed limited clonal diversity and usage of a restricted set of TCR Vbeta regions. Although TCRbeta-chain junctional sequences were highly diverse, a large fraction of NLV/A2-specific T cells derived from distinct individuals showed several recurrent (so-called "public") TCR features associated in some cases with full conservation of the TCRalpha chain junctional region. A dramatic clonal focusing of NLV/A2-specific T cells was observed in situations of HCMV reactivation and/or chronic inflammation, which resulted in selection of a single clonotype displaying similar public TCR features in several patients. In most instances the NLV/A2-specific dominant clonotypes showed higher affinity for their Ag than subdominant ones, thus suggesting that TCR affinity/avidity is the primary driving force underlying repertoire focusing along chronic antigenic stimulation.